Inhibition of SMYD2 Sensitized Cisplatin to Resistant Cells in NSCLC Through Activating p53 Pathway - Shang, Lei; Wei, Minjie (Frontiers in Oncology, 2019)
The protein lysine methyltransferase SMYD2 has recently emerged as a new enzyme modulate gene transcription or signaling pathways, and involved into tumor progression. However, the role of SMYD2 in drug resistant is still not known. Here, we found that inhibition of SMYD2 by specific inhibitor could enhance the cell sensitivity to cisplatin (CDDP), but not paclitaxel, NVB, and VCR in non-small cell lung cancer (NSCLC). Further study showed that SMYD2 and its substrates were overexpressed in NSCLC resistant cells, and the inhibition of SMYD2 or knockdown by specific siRNA could reverse the cell resistance to cisplatin treatment in NSCLC/CDDP cells. In addition, our data indicated that the inhibition or knockdown SMYD2 inhibit tumor sphere formation and reduce cell migration in NSCLC/CDDP cells, but not in NSCLC parental cells. Mechanistically, inhibition of SMYD2 could enhance p53 pathway activity and induce cell apoptosis through regulating its target genes, including p21, GADD45, and Bax. On the contrary, the sensitivity of cells to cisplatin was decreased after knockdown p53 or in p53 deletion NSCLC cells. The synergistically action was further confirmed by in vivo experiments. Taken together, our results demonstrate SMYD2 is involved into cisplatin resistance through regulating p53 pathway, and might become a promising therapeutic target for cisplatin resistance in NSCLC.